Is Co-Occurrence of Frailty and Multimorbidity Associated with Increased Risk of Catastrophic Health Expenditure? A Prospective Cohort Analysis in China - Li H; Chen J; Su D; Xu X; He R (Dove Medical Press, 2023)
Haomiao Li,1 Jiangyun Chen,2 Dai Su,3 Xiwu Xu,4 Ruibo He1,5 1School of Political Science and Public Administration, Wuhan University, Wuhan, Hubei, People's Republic of China; 2Institute of Health Management, Southern Medical University, Guangzhou, Guangdong, People's Republic of China; 3Department of Health Management and Policy, School of Public Health, Capital Medical University, Beijing, People's Republic of China; 4School of Economics and Management, Beijing Jiaotong University, Beijing, People's Republic of China; 5College of Finance and Public Administration, Hubei University of Economics, Wuhan, Hubei, People's Republic of ChinaCorrespondence: Ruibo He, School of Political Science and Public Administration, Wuhan University, Wuhan, Hubei, 430072, People's Republic of China, Email heruibo27@163.comPurpose: The coexistence of multimorbidity and frailty is more likely to increase the risk of physical limitations, mortality and other adverse health outcomes in older adults than their individual occurrence. However, whether and how this coexistence is associated with catastrophic health expenditure (CHE) has not been well assessed. This study aimed to evaluate the independent and coexisting effects of frailty and multimorbidity on CHE.Participants and Methods: A total of 4838 participants obtained from the China Health and Retirement Longitudinal Study (CHARLS) without CHE at baseline (2011) were included in the analytical sample. Marginal structural model (MSM) and time-varying Cox regression model were used to assess the independent and co-occurring impact of frailty and multimorbidity on CHE, respectively.Results: Suffering from single chronic disease (HR, 1.26; 95% CI, 1.13- 1.40; P < 0.001), multimorbidity (HR, 1.80; 95% CI, 1.63- 1.99; P < 0.001) and frailty (HR, 1.32; 95% CI, 1.21- 1.45; P < 0.001) were associated with a higher risk of CHE. Frailty co-occurring with a single chronic disease (HR, 1.28; 95% CI, 1.03- 1.60; P = 0.027) or multimorbidity (HR, 1.91; 95% CI, 1.56- 2.32; P < 0.001), and multimorbidity co-occurring with frailty also increased CHE risk (HR, 1.32; 95% CI, 1.17- 1.48; P < 0.001) compared with single frailty or multimorbidity status.Conclusion: Preventing, postponing, or reducing frailty, and enhancing standard management of chronic diseases are essential in reducing healthcare costs and preventing families from poverty. More efficient interventions for frailty and multimorbidity are urgently required.Keywords: frailty, multimorbidity, catastrophic health expenditure, co-occurrence